Chinese primer : character text - Chʻen, Ta-tuan; Link, Perry, 1944-; Tai, Yih-jian (Princeton language program., 1994)
Four experienced teachers of beginning Chinese have developed this introductory textbook. A pilot edition has been tested widely in classrooms and refined over a period of years. Among its salient features are lessons that are lively, amusing, and relevant to everyday life: concentrated training of ear and tongue in the sound system of Chinese; extensive grammar notes, clearly presented, with attention to mistakes English-speakers are likely to make; a carefully sequenced character workbook embodying a new and effective approach to the learning of Chinese characters; and audiovisual reinforcement via a complete set of audiotapes and two videotapes, one of which offers entertaining dramatizations of the lesson dialogues. The Chinese Primer is available in two versions, one using the GR system of romanization, which employs different spellings instead of diacritical marks for different tones, the other using Pinyin romanization. The contents of the four volumes are as follows: (1) Blue Book [Lessons]: Introduction; foundation work on pronunciation; lesson dialogues in romanized Chinese and English; appendices; glossary-index. (2) Red Book [Notes and Exercises]: Vocabularies; grammar notes and culture notes keyed to the lessons; exercises. (3) Yellow Book [Character Workbook]: workbook. (4) Green Book [Pinyin Character Text]: Texts of the lessons in both traditional and simplified Chinese characters, and a Chinese introduction for teachers. The first three volumes: Blue Book, Red Book, and Yellow Book are sold as a set (GR Set or Pinyin Set). In addition, the GR Blue Book [Lessons], GR Red Book [Notes and Exercises], and GR Yellow Book [Character Workbook], along with the Pinyin Green Book [Pinyin Character Text] are sold separately. The GR Audio and video materials are available from the Chinese Linguistics Project at Princeton University for use with this text. These supplementary materials are not published by Princeton University Press. For further information and prices, contact the Chinese Linguistics Project, 231 Palmer Hall, Princeton University, Princeton, N.J. 08544. (609-258-4269).